Parents' Marital Status, Psychological Counseling and Dishonest Kindergarten Children: An Experimental Study - Yossef Tobol; Gideon Yaniv (Institute of Labor Economics (IZA), 2019)
The present paper reports the results of an experiment which studied the effects of parents' marital status (divorced or non-divorced) and psychological counseling (administered or not) on the honesty level of kindergarten children. Data on marital status and psychological counseling was anonymously provided by the kindergarten teachers and children's level of honesty was assessed by a flip-coin task which rewarded a self-reported favorable outcome. The experiment gave rise to two major results: first, children of divorced parents are less honest than children of non-divorced parents and second, psychological counseling helps improve honesty among children of divorced parents but fails to do so among children of non-divorced parents. No gender effect was found.
Keywords: C91; C92; K42; 330; kindergarten children; dishonest behavior; flip coin task; psychological counseling